Machine Learning in Calorimeter optimization. Issue 1 (January 2021) - Boldyrev, A.; Derkach, D.; Ratnikov, F.; Shevelev, A.
Abstract: The optimization of big industrial setups and the accompanying detailed simulations of internal physical processes require complex and time-consuming simulation calculations. We propose a versatile approach that can alleviate difficulties in solving this problem and show this using an example of electromagnetic calorimeter optimization at a Large Hadron Collider experiment. Our approach consists of a block representation of the calorimeter optimization process from setting sensitive characteristics of modules and their locations to obtaining a quality metric and applying machine learning methods. The main blocks are signal and background particles generation and their propagation to the calorimeter, the generation of electromagnetic showers of signal and noise in modules with a given technology, the combination of signal and noise with the simulation of different luminosities, the energy and spatial reconstruction of the signal and obtaining the final metric. This approach allows us to evaluate the operational characteristics of the calorimeter and find a more suitable configuration with the necessary quality without extensive use of time-consuming resources.